The Effect of Blended Learning Problem-Based Instruction Model on Students’ Critical Thinking Ability in Thermodynamic Course - Marnita, M.; Taufiq, M.; Iskandar, I.; Rahmi, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The course of thermodynamics is one of the subjects whose material content consists of real theory and practice and the use of formulas. Therefore, in the application of this course is a need to apply a learning model that is able to help students find and solve problems and be able to explain their findings in achieving the basic competencies of thermodynamics course. The learning model is a Problem Based Instruction learning model based on Blended Learning. This study aims to improve the critical thinking skills of pre-service physics teacher as a result of using Problem Based Instruction based on Blended Learning in the course of thermodynamics. Retrieval of data in this study was conducted on third semester students of physics education study programs that take Thermodynamics course. This research was conducted in September-October 2019. The research method used is quasi-experimental. Quasi-experiments are research carried out on a single group of students. Data analysis in this study used a one-party t-test. The results showed that (1) the application of the Problem Based Instruction learning model based on Blended Learning can improve students’ critical thinking skills, (2) Students’ responses to the application of the Problem Based Instruction learning model based on Blended Learning get a very happy category of ongoing learning.